Benazir Bhutto, political thinker and diplomat : selected articles, interviews, speeches, editorials, obituaries and book reviews - Bhutto, Benazir, 1953-2007.; Halepoto, Zulfiqar (Karachi : Sindhica : Stockists, Fazlee Book, 2008)
Benazir Bhutto, 1953-2007, former prime minister of Pakistan.
Keywords: Bhutto, Benazir, -- 1953-2007.; Politics and government -- General books; Pakistan -- Politics and government -- 1971-1988.; Pakistan -- Politics and government -- 1988-